Long-term feeding with Euglena gracilis cells modulates immune responses, oxidative balance and metabolic condition in Diplodon chilensis (Mollusca, Bivalvia, Hyriidae) exposed to living Escherichia coli - Bianchi, Virginia Angélica (2015)
We evaluated the modulating effect of long-term feeding with lyophilized Euglena gracilis cells on immune response, oxidative balance and metabolic condition of the freshwater mussel Diplodon chilensis. Mussels, previously fed with Scenedesmus vacuolatus (SV) or E. gracilis (EG) for 90 days, were challenged with an environmentally relevant concentration of Escherichia coli in water for 5 days, under feeding or starvation conditions. EG diet increased overall phagocytic activity and tissue hemocyte accumulation (gill and mantle), and favored hemocyte viability upon E. coli challenge. Tissular hemocyte accumulation, and humoral bacteriolytic activity and protein content were similarly stimulated by EG and E. coli, with no further effect when both stimuli were combined. Both, E. coli challenge and EG diet reduced gill bacteriolytic activity with respect to nonchallenged SV mussels, while no effect was observed in challenged EG mussels. Gill and digestive gland protein contents, along with digestive gland bacteriolytic activity were higher in EG than in SV mussels. Both SV and EG mussels showed increased gill mass upon E. coli challenge, while digestive gland mass was increased by bacterial challenge only in SV mussels. Bacterial challenge produced no effect on humoral reactive oxygen species levels of both groups. Total oxyradical scavenging capacity levels was reduced in challenged SV mussels but remained unaffected in EG ones. In general, EG diet decreased glutathione S-transferase and catalase activities in gill and digestive gland, compared with SV diet; but increased enzyme activity was evident in challenged mussels of both groups. Gill and digestive gland lipid peroxidation levels were higher in EG than in SV mussels but E. coli challenge had stronger effect on SV mussels. Adductor muscle RNA:DNA ratio was higher in EG mussels than in SV ones, and increased upon E. coli challenge in mussels of both groups. E. gracilis can be suggested as a nutritional and protective diet complement suitable for filtering bivalves. However, our results obtained from starved mussels show that starvation periods after supplying this diet should be avoided, since these could revert part of the acquired benefits and/or exacerbate detrimental effects.